Impact of agricultural reforms in Bihar: Test case for new farm laws - Kishore, Avinash; Kishore, Prabhat; Roy, Devesh; Saroj, Sunil (International Growth Centre, 2021)
The 2020 farm laws have been opposed by several farmers due to their possible use for corporate takeover of agriculture, removal of APMC mandis, and dilution of minimum support price and public procurement. This article examines the impact of repealing the Agricultural Produce Marketing Committee Act in Bihar in 2006 on the state’s agricultural indicators – as a test case for the potential impact of the Farmers’ Produce Trade and Commerce (Promotion and Facilitation) Act.